2012
DOI: 10.17221/5955-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the developmental toxicity of 2-phenoxyethanol and clove oil anaesthetics using the Frog Embryo Teratogenesis Assay: Xenopus (FETAX)

Abstract: ABSTRACT:The developmental toxicity of two anaesthetics, 2-phenoxyethanol and clove oil, used in aquaculture was evaluated using the Frog Embryo Teratogenesis Assay: Xenopus (FETAX) and the results were compared to outcomes in fish. Xenopus laevis embryos were exposed to 50, 100, 300, 500, 700 and 1000 mg/l of 2-phenoxyethanol or 1, 5, 10, 20, 30 and 40 mg/l of clove oil. Values of 96 h LC50, 96 h EC50 (malformation) and teratogenic index (ratio of 96 h LC50 and 96 h EC50) were determined and the types and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…(2007) showed that the use of 2-PE at a concentration of 0.30 mL/L did not cause any irreversible damage to sheatfish. ( Vrskova and Modra (2012) reported in 2012 that 2-PE at concentrations higher than 300 mg/L induced embryonic growth inhibition in frogs and posed a teratogenic risk. A 2014 study by ( Mitjana et al., 2014 ; Bonastre et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2007) showed that the use of 2-PE at a concentration of 0.30 mL/L did not cause any irreversible damage to sheatfish. ( Vrskova and Modra (2012) reported in 2012 that 2-PE at concentrations higher than 300 mg/L induced embryonic growth inhibition in frogs and posed a teratogenic risk. A 2014 study by ( Mitjana et al., 2014 ; Bonastre et al.…”
Section: Discussionmentioning
confidence: 99%
“…Velisek et al (2007) showed that the use of 2-PE at a concentration of 0.30 mL/L did not cause any irreversible damage to sheatfish. (Vrskova and Modra (2012) reported in 2012 that 2-PE at concentrations higher than 300 mg/L induced embryonic growth inhibition in frogs and posed a teratogenic risk. A 2014 study by (Mitjana et al, 2014;Bonastre et al 2014) noted that repeated exposure to 2-PE resulted in some tolerance of juvenile angel fish to sedation and anesthetics, indicating that angel fish produce compensatory effects by reducing the number of GABA receptors, thereby prolonging the sedation and anesthesia time.…”
Section: Discussionmentioning
confidence: 99%
“…2-PHE has been used on newts ( Perret & Joly, 2002 ), fishes ( Toni et al, 2015 ), and adult frogs ( Eggert, Peyret & Guyétant, 1999 ) for anesthetic purposes, but has been largely overlooked for larval application. In most amphibian research MS-222 has been used, popularized perhaps because of its use in amphibian medicine ( Mitchell, 2009 ; Vrskova & Modra, 2012 ). Yet, MS-222 needs to be buffered and has been found to increase cortisol concentrations (an indicator of stress) ( Coyle, Durborow & Tidwell, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…CHAPTER FIVE: ACTIVITIES OF EMERGING CONTAMINANTS Collectively, the data from the in vitro yeast bioassay and previous in vivo studies (Voskoboynik et al 2002;Houtman et al 2004a;Vrskova & Modra 2012) highlight the high toxicity of these synthetic chemicals towards a wide range of aquatic organisms. This is of particular concern since these compounds are being detected with increasing frequency in aquatic environments (Daughton & Ternes 1999;Kolpin et al 2004;Kasprzyk-Hordern et al 2008;Kimura et al 2014).…”
Section: )mentioning
confidence: 99%